Importance Of Cantillation (Chanting) –A Divine Remedy In Ayurveda - Prajapati, Neha; Kotecha, Mita; Mishra, Amit; ram, Sukha (International Research Journal of Ayurveda & Yoga, 2020)
The classic texts of Indian origin record the influence of Chanting on plants and animals. Ayurveda also recognises the importance of this realm of medicine. There is a need for an effective stress-reducing intervention, such as mantra meditation. For treatment Charak classified the treatment principle in, 1. Daivavyapasraya chikitsa, 2. Yuktivyapasraya chikitsa, 3. Satvavajaya chikitsa. Mantra – the sound therapy of healing effect on the body, mind and spirit through the movement of tongue, the mouth and it changes the chemical in brain which relaxes the brain wave; detoxify the mind, cleansing the cellular toxin. Chanting instil confidence, improve concentration and sound therapy in the medicine of the future, sound as a carrier wave of consciousness protects us from several diseases and reforms the future.